ANALISIS KELAYAKAN SOSIAL, FINANSIAL DAN PASAR PRODUK HUTAN TANAMAN RAKYAT: STUDI KASUS DI KABUPATEN DOMPU, NUSA TENGGARA BARAT - Subarudi Subarudi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Dompu Regency is one of the regencies in Nusa Tenggara Barat Province that has recieved a license on Community Plantation Forest (CPF) and realized all the targeted areas, and obtained the loan from Center of Financing for Plantation Forest Development, Ministry of Forestry. However, it still faced obstacles and problems in its field operation. Therefore, the review on CPF development in Dompu Regency is needed as a lesson learned. The objectives of the review are: 1) to analyse the social feasibility of CPF management; 2) to analyse the financial feasibility of CPF management and 3) to analyse the market feasibility of CPF management. The results of review indicated that the social feasibility of CPF still faced the problems, namely: 1) CPF program become a legalization of non-permit forest management; 2) CPF program requires an instant and a suddent institutional development; 3) difficulty in working group; 4) inland utilization is not optimum; 5) difficulty in managing group administration system; 6) low quality of human resources in cooperative management and 7) unmeasureable performance of CPF field advisor. Financial aspect of CPF management is feasible with NVP as much as IDR 20,054,791, BCR = 3.31 and IRR = 28%. The CPF market feasibility in Dompu Regency is promising due to high timber demands by sawn timber and furniture industries.